Shang and Zhou Dynasties : The Bronze Age of China - Early Civilization Ancient History for Kids 5th Grade Social Studies - Baby Professor (New York, United Kingdom Baby Professor, 2017)
This book discusses the Shang and Zhou Dynasties, which compose the Bronze Age of China. Who were the personalities known during these times? What were the challenges and successes that the people faced? How did they survive? Reading this book will create a complete picture of the events of the ancient past. Buy a copy today!